Thinking twice about the evolution of photosynthesis - Cardona,Londono T (Open Biology, 2019)
Sam Granick opened his seminal 1957 paper titled ‘Speculations on the origins and evolution of photosynthesis’ with the assertion that there is a constant urge in human beings to seek beginnings (I concur). This urge has led to an incessant stream of speculative ideas and debates on the evolution of photosynthesis that started in the first half of the twentieth century and shows no signs of abating. Some of these speculative ideas have become commonplace, are taken as fact, but find little support. Here, I review and scrutinize three widely accepted ideas that underpin the current study of the evolution of photosynthesis: first, that the photochemical reaction centres used in anoxygenic photosynthesis are more primitive than those in oxygenic photosynthesis; second, that the probability of acquiring photosynthesis via horizontal gene transfer is greater than the probability of losing photosynthesis; and third, and most important, that the origin of anoxygenic photosynthesis pre-dates the origin of oxygenic photosynthesis. I shall attempt to demonstrate that these three ideas are often grounded in incorrect assumptions built on more assumptions with no experimental or observational support. I hope that this brief review will not only serve as a cautionary tale but also that it will open new avenues of research aimed at disentangling the complex evolution of photosynthesis and its impact on the early history of life and the planet.